Pengembangan Teknologi Informasi Dan Komunikasi Di Bidang Kesiswaan, Kepegawaian Dan Keuangan Di Sma Muhammadiyah 1 Gresik - Muchamad Suradji (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
The development of information and communication technology has indirectly influenced the world of education and learning in this country. These developments are fundamental and have brought significant changes in the acceleration and innovation of education. However, in addressing these developments, not all parties or circles are able to respond well. Therefore, to be able to give a positive impact, one that needs to be done is the development of information and communication technology that is done through the utilization of ICT in education that includes the role of ICT as the substance of education, learning aids, educational facilities, competency standards, administrative support education, education unit management tools, and educational infrastructure. This research is a qualitative descriptive research. The method of data collection is: observation, interview and documentation. Data analysis technique using qualitative analysis. The steps in data analysis techniques include, data reduction, data display and verification. The results of this study can be concluded that the development of information and communication technology in the field of student affairs in SMA Muhammadiyah 1 Gresik applied in terms of: acceptance of new students, reporting of learning outcomes, and student discipline control. In the field of personnel, technology is developed in terms of employee planning and staffing assessment. While in the field of finance is developing services in the field of finance by working with Bank BRI Syari’ah.